An Fe 0.64 Ni 0.36 / NiFe2O4-CDs bifunctional oxygen electrocatalyst and preparation method and application thereof
Patent Information
- Application Number
- CN202611165889.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-09
AI Technical Summary
[0007]针对现有技术中锌空气电池空气阴极催化剂ORR/OER反应动力学缓慢、双功能活性难以兼顾、界面结构稳定性不足以及宽温工作性能有限的问题,本发明目的在于提供一种碳点(CDs)稳定Fe0.64Ni0.36/NiFe2O4异质结构调控的双功能ORR/OER催化剂的制备方法,获得Fe0.64Ni0.36/NiFe2O4多孔碳基氧电催化材料;制备过程中利用碳点、碳基载体促进NiFe2O4氧化物相的生成,并抑制金属活性组分的过度团聚,使Fe0.64Ni0.36合金相与NiFe2O4氧化物相形成稳定的异质界面;同时,碳点可调节碳基载体表面电子结构,增强Fe0.64Ni0.36/NiFe2O4界面电子耦合作用,应用于锌空气电池,提高空气阴极催化剂ORR和OER反应动力学
1、本发明通过构建Fe0.64Ni0.36/NiFe2O4异质结构,使金属合金位点和双金属氧化物位点形成协同催化作用,有利于同时提升ORR和OER双功能催化性能。
Smart Images

Figure CN122889769A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrocatalysis technology, specifically relating to a Fe 0.64 Ni 0.36 / NiFe2O4-CDs bifunctional oxygen electrocatalysts, their preparation methods, and applications. Background Technology
[0002] With the development of sustainable clean energy systems, electrochemical energy conversion and storage technologies have received widespread attention. Novel energy devices such as water electrolysis devices, fuel cells, and metal-air batteries have significant application prospects in improving energy utilization efficiency and reducing dependence on fossil fuels. Among them, rechargeable zinc-air batteries are considered a promising energy storage device due to their advantages such as high theoretical energy density, abundant zinc resources, low cost, and good safety.
[0003] However, the practical application of zinc-air batteries is still limited by the slow reaction kinetics of the air cathode. During charge and discharge, the air cathode mainly involves the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). Since both ORR and OER are multi-electron transfer processes, their reaction pathways are complex and their kinetic rates are slow, easily leading to high overpotentials and low energy conversion efficiency. Especially under wide-temperature or low-temperature operating conditions, the catalyst's ion transport capacity decreases, further slowing down the oxygen reaction kinetics, resulting in a significant reduction in the output performance and cycle stability of the zinc-air battery. Therefore, developing air cathode catalytic materials that combine high ORR / OER bifunctional catalytic activity, good stability, and wide-temperature adaptability is key to improving the practical application performance of zinc-air batteries.
[0004] Currently, noble metal-based catalysts such as platinum-based, ruthenium-based, and iridium-based materials exhibit high catalytic activity in ORR or OER, but their high cost and scarcity, coupled with the difficulty in simultaneously achieving bifunctional catalytic performance in both ORR and OER, limit their large-scale application. In contrast, transition metals and their oxides are widely used in the construction of oxygen electrocatalytic materials due to their abundant resources, lower cost, tunable valence states, and designable electronic structures. However, single transition metal oxides typically suffer from insufficient conductivity, high intrinsic reaction barriers, and limited utilization of active sites; while single transition metals or alloys exhibit good conductivity, they are prone to structural reconstruction, aggregation, or oxidative deactivation during long-term electrochemical reactions, leading to decreased catalytic activity and cycle stability.
[0005] To address these issues, previous studies have attempted to construct transition metal / transition metal oxide heterostructures. These heterostructures utilize interfacial coupling effects to modulate electronic structures, promoting the adsorption of reaction intermediates and charge transfer, thereby enhancing oxygen electrocatalytic performance. However, existing TMs / TMOs heterostructure catalysts still suffer from problems such as insufficient interfacial bonding stability, discontinuous electron transport pathways, easy migration or aggregation of metal active sites, and significant catalytic kinetic decay at low temperatures. Especially during the long-term charge-discharge process of rechargeable zinc-air batteries, the catalyst needs to withstand both reduction and oxidation reaction environments simultaneously. Ordinary heterostructures struggle to maintain stable interfacial electronic regulation over extended periods, thus affecting the battery's cycle life and wide-temperature operating performance.
[0006] Carbon nanomaterials possess excellent electrical conductivity, large specific surface area, and tunable surface chemical structures, making them important supports for loading and regulating metal active sites. Among these, carbon dots, with their small size, abundant surface functional groups, and strong electronic modulation capabilities, hold promise for regulating the local electronic structure of metal / metal oxide interfaces and enhancing the interaction between active components and carbon-based supports. However, how to utilize carbon dots to stabilize bimetallic alloy / bimetallic oxide heterojunction interfaces and further achieve synergistic regulation of ORR and OER bifunctional active sites remains a problem to be solved in current technologies. Therefore, there is an urgent need to develop an air cathode catalyst material that is structurally stable, low-cost, simple to prepare, and possesses high bifunctional oxygen electrocatalytic activity and wide temperature adaptability to address the problems of slow reaction kinetics, insufficient cycle stability, and severe low-temperature performance degradation of existing zinc-air battery air cathode catalysts. Summary of the Invention
[0007] To address the problems of slow ORR / OER reaction kinetics, difficulty in achieving dual-functionality, insufficient interfacial structural stability, and limited wide-temperature operating performance of air cathode catalysts in existing zinc-air batteries, this invention aims to provide a carbon dot (CDs) stabilized Fe 0.64 Ni 0.36 A method for preparing bifunctional ORR / OER catalysts regulated by the heterostructure of NiFe2O4, obtaining Fe 0.64 Ni 0.36 / NiFe2O4 porous carbon-based oxygen electrocatalyst material; during preparation, carbon dots and carbon-based supports are used to promote the formation of the NiFe2O4 oxide phase and inhibit the excessive aggregation of the metal active components, so that Fe 0.64 Ni 0.36 The alloy phase forms a stable heterogeneous interface with the NiFe2O4 oxide phase; simultaneously, carbon dots can modulate the electronic structure of the carbon-based support surface, enhancing Fe... 0.64 Ni 0.36 The electronic coupling effect at the NiFe2O4 interface is applied to zinc-air batteries to improve the reaction kinetics of ORR and OER of the air cathode catalyst.
[0008] In a first aspect, the present invention provides an Fe 0.64 Ni 0.36 The preparation method of / NiFe2O4-CDs bifunctional oxygen electrocatalyst includes the following steps: (1) Melamine was placed in a crucible and sealed. Then the crucible was moved into a muffle furnace and sintered for the first time under a closed reaction environment. The thermal polymerization formed graphite-like carbon nitride. After sintering, the furnace was naturally cooled to room temperature. The product was taken out and ground into fine powder. The fine powder was put back into the crucible and sealed. The second sintering was carried out under a closed reaction environment. The carbon nanosheets were obtained by naturally cooling to room temperature. (2) Prepare a mixed solvent using deionized water, ethanol and methanol, then dissolve the iron source, nickel source, carbon dot precursor and carbon nanosheets in the mixed solvent, and ultrasonically disperse them to form a uniform mixed solution. Then transfer the obtained mixed solution to the reaction vessel, put it in the oven for reaction, and cool it at room temperature after the reaction is completed. (3) The cooled solution is dried, and the resulting block sample is ground to obtain a fine powder sample; (4) Under an inert protective atmosphere, the powder sample was subjected to a high-temperature pyrolysis reduction reaction. After the reaction was completed, it was cooled to room temperature to obtain Fe. 0.64 Ni 0.36 / NiFe2O4-CDs bifunctional oxygen electrocatalyst.
[0009] Furthermore, in step (1), the heating rate of the first sintering is 2.5℃ / min~3℃ / min, the temperature is raised to 550℃~580℃ and held for 4h~6h; the heating rate of the second sintering is 8℃ / min~10℃ / min, the temperature is raised to 500℃~550℃ and held for 2h~3h.
[0010] Further, in step (2), the ratio of iron source, nickel source, carbon dot precursor and carbon nanosheet is (3.2~6.3):(3.1~5.1):(3.1~5.1):100, and the iron source, nickel source, carbon dot precursor and carbon nanosheet form a solid mixture. The volume ratio of the sum of the molar amounts of iron source, nickel source and carbon dot precursor to the volume of the mixed solvent is (15.7~27.9):(50~60). The ultrasonic dispersion time is 0.5h to 1h, the reaction temperature in the oven is 160℃ to 180℃, and the reaction time is 6h to 8h.
[0011] Further, in step (2), the iron source is a mixture of Fe(NO3)3·9H2O, FeSO4·7H2O, C6H8O7Fe and FePO4, and the nickel source is a mixture of Ni(NO3)2·6H2O, NiSO4·6H2O and C6H8O7Fe and FePO4. 10 H 14 A mixture of NiO4, with carbon dot precursors being a mixture of citric acid, o-phenylenediamine, and urea.
[0012] Furthermore, the molar ratio of Fe(NO3)3·9H2O, FeSO4·7H2O, C6H8O7Fe and FePO4 is (2~4):(1~2):(0.1~0.2):0.1; Ni(NO3)2·6H2O, NiSO4·6H2O and C 10 H 14 The molar ratio of NiO4 is (2-3):(1-2):0.1; The molar ratio of citric acid, urea, and o-phenylenediamine is (1-2):(2-3):0.1; The volume ratio of deionized water, ethanol and methanol is (1-3):(1-3):(1-3).
[0013] Furthermore, in step (3), the drying temperature is 80℃~90℃, the drying time is 12h~15h, and the grinding time is 20min~30min.
[0014] Furthermore, in step (4), the mixed protective gas is a mixture of Ar and N2, and the volume ratio of Ar to N2 is (50-70):1; The high-temperature pyrolysis reduction reaction is carried out in a tube furnace. The tube furnace is heated to 850℃~900℃ at a heating rate of 2℃ / min~3℃ / min and held at that temperature for 2h~3h.
[0015] Secondly, the present invention provides an Fe 0.64 Ni 0.36 / NiFe2O4-CDs bifunctional oxygen electrocatalyst, using the above-mentioned Fe 0.64 Ni 0.36 The / NiFe2O4-CDs bifunctional oxygen electrocatalyst was prepared by a method for preparing the Fe 0.64 Ni 0.36 / NiFe2O4-CDs bifunctional oxygen electrocatalyst is a heterostructured porous carbon-based oxygen electrocatalytic material; Fe 0.64 Ni 0.36 Oxygen electrocatalytic performance of / NiFe2O4-CDs bifunctional oxygen electrocatalyst: Electrochemical ORR and OER were tested on a Bio-logic VMP-300 electrochemical station, with Fe 0.64 Ni0.36 The NiFe2O4-CDs catalyst was used as the working electrode, the Hg / HgO electrode as the reference electrode, and the Pt electrode as the counter electrode. Electrochemical ORR and OER were measured using 0.1 mol / L KOH and 1 mol / L KOH solutions as electrolytes, respectively. For ORR, the half-wave potential (E...) 1 / 2 The voltage reaches 0.854V to 0.86V; for OER, 10mA / cm 2 At current density, the overpotential is 280mV to 300mV.
[0016] Thirdly, the present invention provides an Fe 0.64 Ni 0.36 Application of / NiFe2O4-CDs bifunctional oxygen electrocatalyst in zinc-air batteries.
[0017] Furthermore, with Fe 0.64 Ni 0.36 A liquid zinc-air battery was assembled using a NiFe2O4-CDs bifunctional oxygen electrocatalyst as the air cathode and a zinc sheet as the anode in a 6 mol / L KOH + 0.2 mol / L Zn(CH3COO)2 electrolyte. The battery operates at 20 mA / cm². 2 At current density, it achieves stable cycling for over 585 hours, with a power density ≥214.7 mW / cm². 2 A solid-state zinc-air battery was then assembled using sodium polyacrylate as the electrolyte, and tested at a low temperature of -40℃ and a current of 2 mA / cm². 2 Stable cycling for more than 390 hours at current density.
[0018] Advantages and effects of the present invention: 1. This invention constructs Fe 0.64 Ni 0.36 The / NiFe2O4 heterostructure enables the metal alloy sites and bimetallic oxide sites to form a synergistic catalytic effect, which is beneficial to simultaneously improve the bifunctional catalytic performance of ORR and OER.
[0019] 2. This invention introduces carbon dots to modify and stabilize heterogeneous interfaces, which can promote Fe... 0.64 Ni 0.36 The electronic interaction between the substance and NiFe2O4 improves the local charge distribution and reduces the kinetic resistance in the oxygen electrocatalytic reaction process.
[0020] 3. The present invention uses a porous carbon-based structure as a conductive framework, which is beneficial to improve the conductivity of the catalyst, increase the number of exposed active sites, and improve the transport process of oxygen, electrolyte and reaction intermediates.
[0021] 4. The Fe prepared by this invention 0.64 Ni 0.36When NiFe2O4 catalyst is used in the air cathode of zinc-air batteries, it can reduce air electrode polarization, improve battery energy efficiency and cycle stability, and exhibit good wide temperature adaptability.
[0022] 5. The preparation method of this invention is simple, the raw materials are widely available, and the cost is low, making it suitable for the preparation of high-performance rechargeable zinc-air battery air cathode catalytic materials. Attached Figure Description
[0023] Figure 1 Fe was prepared in Example 1 0.64 Ni 0.36 Scanning electron microscope (SEM) image of NiFe2O4-CDs bifunctional oxygen electrocatalyst; Figure 2 Fe was prepared in Example 1 0.64 Ni 0.36 / NiFe2O4-CDs bifunctional oxygen electrocatalyst was used as an air cathode to assemble a liquid zinc-air battery at 20 mA / cm 2 Charge-discharge performance curves at current density; Figure 3 Fe was prepared in Example 1 0.64 Ni 0.36 Electrodeization test curves of liquid zinc-air batteries assembled with NiFe2O4-CDs bifunctional oxygen electrocatalyst as air cathode. Figure 4 Fe was prepared in Example 1 0.64 Ni 0.36 A solid-state zinc-air battery assembled using NiFe2O4-CDs bifunctional oxygen electrocatalyst as an air cathode achieved a performance of 2 mA / cm² at a low temperature of -40℃. 2 Charge-discharge performance curves at current density. Detailed Implementation
[0024] The specific embodiments of the present invention will be described in further detail below with reference to the accompanying drawings and examples.
[0025] A Fe 0.64 Ni 0.36 The preparation method of / NiFe2O4-CDs bifunctional oxygen electrocatalyst includes the following steps: (1) Weigh melamine and place it in a crucible, cover it and seal it with aluminum foil to form a closed reaction environment to prevent the material from volatilizing during the thermal polymerization process; then move the crucible into a muffle furnace and carry out the first sintering in a closed reaction environment. The temperature is raised to 550℃~580℃ at a heating rate of 2.5℃ / min~3℃ / min and held for 4h~6h to form graphite-like carbon nitride through thermal polymerization; after sintering, the furnace is naturally cooled to room temperature, the product is taken out and ground into fine powder; the obtained fine powder is put back into the crucible and sealed, and carried out the second sintering in a closed reaction environment. The temperature is raised to 500℃~550℃ at a heating rate of 8℃ / min~10℃ / min and held for 2h~3h to further peel and refine the material. The carbon nanosheets are obtained by naturally cooling to room temperature.
[0026] (2) Deionized water, ethanol, and methanol are mixed in a volume ratio of (1-3):(1-3):(1-3) to form a mixed solvent. Solid iron source, nickel source, carbon dot precursor, and carbon nanosheets are then dissolved in the mixed solvent. The ratio of iron source, nickel source, carbon dot precursor, and carbon nanosheets (mmol:mmol:mmol:mg) is (3.2-6.3):(3.1-5.1):(3.1-5.1):100. The iron source, nickel source, carbon dot precursor, and carbon nanosheets form a solid mixture. The volume ratio of the sum of the molar amounts of the iron source, nickel source, and carbon dot precursor to the volume of the mixed solvent (mmol:mg) is... The ratio of L is (15.7~27.9):(50~60). The mixture is ultrasonically dispersed for 0.5h~1h to form a homogeneous solution. The resulting solution is then transferred to a reaction vessel and placed in an oven at 160℃~180℃ for 6h~8h. After the reaction is complete, the mixture is cooled to room temperature. The iron source is a mixture of Fe(NO3)3·9H2O, FeSO4·7H2O, C6H8O7Fe, and FePO4 in a molar ratio of (2~4):(1~2):(0.1~0.2):0.1. The nickel source is a mixture of Ni(NO3)2·6H2O, NiSO4·6H2O, and C6H8O7Fe. 10 H 14 NiO4 is a mixture formed in a molar ratio of (2-3):(1-2):0.1; the carbon dot precursor is a mixture formed in a molar ratio of citric acid, o-phenylenediamine and urea in a molar ratio of (1-2):(2-3):0.1.
[0027] (3) Dry the cooled solution at 80℃~90℃ for 12h~15h, and grind the resulting block sample for 20min~30min to obtain a fine powder sample.
[0028] (4) Place the powder sample in a crucible and then transfer it to a tube furnace. Under a protective atmosphere formed by Ar and N2 in a volume ratio of (50-70):1, heat the sample to 850-900℃ at a heating rate of 2℃ / min-3℃ / min, hold for 2-3 hours, and carry out a high-temperature pyrolysis reduction reaction. After the reaction is completed, cool the sample to room temperature to obtain Fe. 0.64 Ni 0.36 / NiFe2O4-CDs bifunctional oxygen electrocatalyst.
[0029] A Fe 0.64 Ni 0.36 / NiFe2O4-CDs bifunctional oxygen electrocatalyst, using the above-mentioned Fe 0.64 Ni 0.36 The / NiFe2O4-CDs bifunctional oxygen electrocatalyst was prepared by a method for preparing the Fe 0.64 Ni 0.36 / NiFe2O4-CDs bifunctional oxygen electrocatalyst is a heterostructured porous carbon-based oxygen electrocatalytic material.
[0030] To evaluate the Fe of the present invention 0.64 Ni 0.36 The oxygen electrocatalytic performance of the / NiFe2O4-CDs bifunctional oxygen electrocatalyst was assessed by telephone performance testing; electrochemical ORR and OER were tested on a Bio-logic VMP-300 electrochemical station: with Fe 0.64 Ni 0.36 The NiFe2O4-CDs catalyst was used as the working electrode, the Hg / HgO electrode as the reference electrode, and the Pt electrode as the counter electrode. Electrochemical ORR and OER were measured using 0.1 mol / L KOH and 1 mol / L KOH solutions as electrolytes, respectively. For ORR, the half-wave potential (E...) 1 / 2 The voltage reaches 0.854V to 0.86V; for OER, 10mA / cm 2 At current density, the overpotential is 280mV to 300mV.
[0031] A Fe 0.64 Ni 0.36 Application of / NiFe2O4-CDs bifunctional oxygen electrocatalyst in zinc-air batteries.
[0032] To evaluate the Fe of the present invention 0.64 Ni 0.36 The application effect of NiFe2O4-CDs bifunctional oxygen electrocatalyst in zinc-air batteries was tested after assembling liquid or solid zinc-air batteries; with Fe 0.64 Ni 0.36A liquid zinc-air battery was assembled using a NiFe2O4-CDs bifunctional oxygen electrocatalyst as the air cathode and a zinc sheet as the anode in a 6 mol / L KOH + 0.2 mol / L Zn(CH3COO)2 electrolyte. The battery operates at 20 mA / cm². 2 At current density, it achieves stable cycling for over 585 hours, with a power density ≥214.7 mW / cm². 2 A solid-state zinc-air battery was then assembled using sodium polyacrylate as the electrolyte, and tested at a low temperature of -40℃ and a current of 2 mA / cm². 2 Stable cycling for more than 390 hours at current density.
[0033] Example 1 A Fe 0.64 Ni 0.36 The preparation method of / NiFe2O4-CDs bifunctional oxygen electrocatalyst includes the following steps: (1) Weigh 10g of melamine and place it in a crucible. Cover the crucible and seal it with aluminum foil. Then, transfer the crucible into a muffle furnace. Under a closed reaction environment, heat the crucible to 550℃ at a heating rate of 2.5℃ / min and hold it for 4h. The thermal polymerization forms a graphite-like carbon nitride. After naturally cooling to room temperature, take out the product and grind it into fine powder. Then, put the fine powder into a crucible and seal it. Under a closed reaction environment, heat the crucible to 500℃ at a heating rate of 8℃ / min and hold it for 2h. After naturally cooling to room temperature, carbon nanosheets are obtained.
[0034] (2) A mixed solvent was prepared by mixing deionized water, ethanol, and methanol in a volume ratio of 1:1:1. Then, solid iron source (2 mmol Fe(NO3)3·9H2O + 1 mmol FeSO4·7H2O + 0.1 mmol C6H8O7Fe + 0.1 mmol FePO4) and nickel source (2 mmol Ni(NO3)2·6H2O + 1 mmol NiSO4·6H2O + 0.1 mmol C6H8O7Fe + 0.1 mmol FePO4) were added. 10 H 14 NiO4), carbon dot precursor (1 mmol citric acid + 2 mmol urea + 0.1 mmol o-phenylenediamine) and carbon nanosheets (100 mg) were dissolved in 50 mL of mixed solvent and ultrasonically dispersed for 0.5 h to form a homogeneous mixed solution. The resulting mixed solution was then transferred to a reaction vessel and placed in an oven at 160 °C for 6 h. After the reaction was completed, the mixture was cooled to room temperature.
[0035] (3) Transfer the cooled solution to a beaker, place it in a drying oven, and dry it at 80°C for 12 hours. Grind the resulting block sample for 20 minutes to obtain a fine powder sample.
[0036] (4) Place the powder sample in a crucible and then transfer it to a tube furnace. Under a protective atmosphere of Ar and N2 mixed gas (Ar to N2 volume ratio of 50:1), heat the sample to 850℃ at a rate of 2℃ / min and hold for 2 hours to carry out a high-temperature pyrolysis reduction reaction. After the reaction is completed, cool the sample to room temperature to obtain Fe. 0.64 Ni 0.36 / NiFe2O4-CDs bifunctional oxygen electrocatalyst.
[0037] Fe prepared in Example 1 0.64 Ni 0.36 / NiFe2O4-CDs bifunctional oxygen electrocatalyst is a porous carbon-based oxygen electrocatalytic material. Its morphology and structure were observed using SEM, such as... Figure 1 As shown, Fe can be seen 0.64 Ni 0.36 / NiFe2O4-CDs have a two-dimensional nanosheet structure with abundant pores on their surface, which helps to increase the number of exposed active sites and improve electron transport efficiency, thereby promoting oxygen electrocatalytic reactions.
[0038] Fe prepared in Example 1 0.64 Ni 0.36 The / NiFe2O4-CDs bifunctional oxygen electrocatalyst was tested using a Bio-logic VMP-300 electrochemical station, with Fe as the working electrode. 0.64 Ni 0.36 / NiFe2O4-CDs, reference electrode Hg / HgO, counter electrode Pt; ORR uses 0.1 mol / L KOH, OER uses 1 mol / L KOH; ORR half-wave potential E 1 / 2 The voltage is 0.858V, and the OER is 10mA / cm. 2 The overpotential is 285mV.
[0039] The Fe obtained in Example 1 0.64 Ni 0.36 A liquid zinc-air battery was assembled using a NiFe2O4-CDs bifunctional oxygen electrocatalyst as the air cathode and a zinc sheet as the anode in a 6 mol / L KOH + 0.2 mol / L Zn(CH3COO)2 electrolyte. Charge-discharge cycle performance tests were conducted, and the curves are shown below. Figure 2 As shown, it can be seen at 20mA / cm 2 It can stably cycle for 600 hours at current density; discharge polarization tests were performed, such as... Figure 3 As shown, the peak power density is 222 mW / cm². 2 A solid-state zinc-air battery assembled using sodium polyacrylate as the electrolyte was then subjected to charge-discharge cycle performance testing at a low temperature (-40°C). Figure 4As shown, it can be seen at 2mA / cm 2 It can cycle stably for 400 hours at current density.
[0040] Example 2 A Fe 0.64 Ni 0.36 The preparation method of / NiFe2O4-CDs bifunctional oxygen electrocatalyst includes the following steps: (1) Weigh 10g of melamine and place it in a crucible. Cover the crucible and seal it with aluminum foil. Then, transfer the crucible into a muffle furnace. Under a closed reaction environment, heat the crucible to 550℃ at a heating rate of 2.58℃ / min and hold it for 4.3h. The thermal polymerization forms graphite-like carbon nitride. After naturally cooling to room temperature, take out the product and grind it into fine powder. Then, put the fine powder into a crucible and seal it. Under a closed reaction environment, heat the crucible to 508℃ at a heating rate of 8.3℃ / min and hold it for 2.15h. After naturally cooling to room temperature, carbon nanosheets are obtained.
[0041] (2) A mixed solvent was prepared by mixing deionized water, ethanol, and methanol in a volume ratio of 1:2:3. Then, solid iron source (2.3 mmol Fe(NO3)3·9H2O + 1.15 mmol FeSO4·7H2O + 0.11 mmol C6H8O7Fe + 0.1 mmol FePO4) and nickel source (2.15 mmol Ni(NO3)2·6H2O + 1.15 mmol NiSO4·6H2O + 0.1 mmol C6H8O7Fe + 0.1 mmol FePO4) were added. 10 H 14 NiO4), carbon dot precursor (1.15 mmol citric acid + 2.15 mmol urea + 0.1 mmol o-phenylenediamine) and carbon nanosheets (100 mg) were dissolved in 52 mL of mixed solvent and ultrasonically dispersed for 0.58 h to form a homogeneous mixed solution. The resulting mixed solution was then transferred to a reaction vessel and placed in an oven at 163 °C for 6.3 h. After the reaction was completed, the mixture was cooled to room temperature.
[0042] (3) Transfer the cooled solution to a beaker, place it in a drying oven, and dry it at 82°C for 12.5 h. After drying, grind the block sample for 22 min to obtain a fine powder sample.
[0043] (4) The powder sample was placed in a crucible and then transferred to a tube furnace. Under the protective atmosphere of a mixture of Ar and N2 (Ar to N2 volume ratio of 53:1), the temperature was increased to 858℃ at 2.22℃ / min and held for 2.2h to carry out a high-temperature pyrolysis reduction reaction. After the reaction was completed, the sample was cooled to room temperature to obtain Fe. 0.64 Ni 0.36 / NiFe2O4-CDs bifunctional oxygen electrocatalyst.
[0044] Fe prepared in Example 2 0.64 Ni 0.36 The / NiFe2O4-CDs bifunctional oxygen electrocatalyst was tested using a Bio-logic VMP-300 electrochemical station, with Fe as the working electrode. 0.64 Ni 0.36 / NiFe2O4-CDs, reference electrode Hg / HgO, counter electrode Pt; ORR uses 0.1mol / L KOH, OER uses 1mol / L KOH; ORR half-wave potential E 1 / 2 The voltage is 0.855V, and the OER is 10mA / cm. 2 The overpotential is 289mV.
[0045] The Fe obtained in Example 2 0.64 Ni 0.36 A liquid zinc-air battery was assembled using a NiFe2O4-CDs bifunctional oxygen electrocatalyst as the air cathode and a zinc sheet as the anode in a 6 mol / L KOH + 0.2 mol / L Zn(CH3COO)2 electrolyte. Charge-discharge cycle performance was tested at 20 mA / cm². 2 It can cycle stably for 585 hours under constant current density; discharge polarization and power density tests were conducted, and the peak power density was 214.7 mW / cm². 2 A solid-state zinc-air battery assembled with sodium polyacrylate as the electrolyte was then subjected to charge-discharge cycle performance testing at a low temperature (-40℃), achieving a value of 2 mA / cm². 2 It can cycle stably for 390 hours at current density.
[0046] Example 3 A Fe 0.64 Ni 0.36 The preparation method of / NiFe2O4-CDs bifunctional oxygen electrocatalyst includes the following steps: (1) Weigh 10g of melamine and place it in a crucible. Cover the crucible and seal it with aluminum foil. Then, transfer the crucible into a muffle furnace. Under a closed reaction environment, heat the crucible to 560℃ at a heating rate of 2.6℃ / min and hold it for 4.6h. Thermal polymerization forms graphite-like carbon nitride. After naturally cooling to room temperature, take out the product and grind it into fine powder. Then, put the fine powder into a crucible and seal it. Under a closed reaction environment, heat the crucible to 516℃ at a heating rate of 8.6℃ / min and hold it for 2.3h. After naturally cooling to room temperature, carbon nanosheets are obtained.
[0047] (2) A mixed solvent was prepared by mixing deionized water, ethanol, and methanol in a volume ratio of 2:1:3. Then, a solid iron source (2.6 mmol Fe(NO3)3·9H2O + 1.3 mmol FeSO4·7H2O + 0.12 mmol C6H8O7Fe + 0.1 mmol FePO4) and a nickel source (2.3 mmol Ni(NO3)2·6H2O + 1.3 mmol NiSO4·6H2O + 0.1 mmol C6H8O7Fe + 0.1 mmol FePO4) were added. 10 H 14 NiO4), carbon dot precursor (1.3 mmol citric acid + 2.3 mmol urea + 0.1 mmol o-phenylenediamine) and carbon nanosheets (100 mg) were dissolved in 54 mL of mixed solvent and ultrasonically dispersed for 0.6 h to form a homogeneous mixed solution. The resulting mixed solution was then transferred to a reaction vessel and placed in an oven at 166 °C for 6.6 h. After the reaction was completed, the mixture was cooled to room temperature.
[0048] (3) Transfer the cooled solution to a beaker, place it in a drying oven, and dry it at 84°C for 13 hours. Grind the resulting block sample for 24 minutes to obtain a fine powder sample.
[0049] (4) The powder sample was placed in a crucible and then transferred to a tube furnace. Under the protective atmosphere of a mixture of Ar and N2 (Ar to N2 volume ratio of 56:1), the temperature was increased to 866℃ at 2.4℃ / min and held for 2.4h to carry out a high-temperature pyrolysis reduction reaction. After the reaction was completed, the sample was cooled to room temperature to obtain Fe. 0.64 Ni 0.36 / NiFe2O4-CDs bifunctional oxygen electrocatalyst.
[0050] Fe prepared in Example 3 0.64 Ni 0.36 The / NiFe2O4-CDs bifunctional oxygen electrocatalyst was tested using a Bio-logic VMP-300 electrochemical station, with Fe as the working electrode. 0.64 Ni 0.36 / NiFe2O4-CDs, reference electrode Hg / HgO, counter electrode Pt; ORR uses 0.1mol / L KOH, OER uses 1mol / L KOH; ORR half-wave potential E 1 / 2 The voltage is 0.856V, and the OER is 10mA / cm. 2 The overpotential is 287mV.
[0051] The Fe obtained in Example 3 0.64 Ni 0.36A liquid zinc-air battery was assembled using a NiFe2O4-CDs bifunctional oxygen electrocatalyst as the air cathode and a zinc sheet as the anode in a 6 mol / L KOH + 0.2 mol / L Zn(CH3COO)2 electrolyte. Charge-discharge cycle performance was tested at 20 mA / cm². 2 It can cycle stably for 590 hours under constant current density; discharge polarization and power density tests were conducted, with a peak power density of 215 mW / cm². 2 A solid-state zinc-air battery assembled with sodium polyacrylate as the electrolyte was then subjected to charge-discharge cycle performance testing at a low temperature (-40℃), achieving a value of 2 mA / cm². 2 It can cycle stably for 400 hours at current density.
[0052] Example 4 A Fe 0.64 Ni 0.36 The preparation method of / NiFe2O4-CDs bifunctional oxygen electrocatalyst includes the following steps: (1) Weigh 10g of melamine and place it in a crucible. Cover the crucible and seal it with aluminum foil. Then, transfer the crucible into a muffle furnace. Under a closed reaction environment, heat the crucible to 565℃ at a heating rate of 2.7℃ / min and hold it for 4.9h. Thermally polymerize to form graphite-like carbon nitride. After naturally cooling to room temperature, take out the product and grind it into fine powder. Then, put the fine powder into a crucible and seal it. Under a closed reaction environment, heat the crucible to 524℃ at a heating rate of 8.9℃ / min and hold it for 2.45h. After naturally cooling to room temperature, carbon nanosheets are obtained.
[0053] (2) A mixed solvent was prepared by mixing deionized water, ethanol, and methanol in a volume ratio of 1:1:1. Then, solid iron source (2.9 mmol Fe(NO3)3·9H2O + 1.45 mmol FeSO4·7H2O + 0.13 mmol C6H8O7Fe + 0.1 mmol FePO4) and nickel source (2.45 mmol Ni(NO3)2·6H2O + 1.45 mmol NiSO4·6H2O + 0.1 mmol C6H8O7Fe + 0.1 mmol FePO4) were added. 10 H 14 NiO4), carbon dot precursor (1.45 mmol citric acid + 2.45 mmol urea + 0.1 mmol o-phenylenediamine) and carbon nanosheets (100 mg) were dissolved in 55 mL of mixed solvent and ultrasonically dispersed for 0.74 h to form a homogeneous mixed solution. The resulting mixed solution was then transferred to a reaction vessel and placed in an oven at 170 °C for 7 h. After the reaction was completed, the mixture was cooled to room temperature.
[0054] (3) Transfer the cooled solution to a beaker, place it in a drying oven, and dry it at 86°C for 13.5 h. After drying, grind the block sample for 26 min to obtain a fine powder sample.
[0055] (4) The powder sample was placed in a crucible and then transferred to a tube furnace. Under the protective atmosphere of a mixture of Ar and N2 (Ar to N2 volume ratio of 60:1), the temperature was increased to 874℃ at 2.6℃ / min and held for 2.6h to carry out a high-temperature pyrolysis reduction reaction. After the reaction was completed, the sample was cooled to room temperature to obtain Fe. 0.64 Ni 0.36 / NiFe2O4-CDs bifunctional oxygen electrocatalyst.
[0056] Fe prepared in Example 4 0.64 Ni 0.36 The / NiFe2O4-CDs bifunctional oxygen electrocatalyst was tested using a Bio-logic VMP-300 electrochemical station, with Fe as the working electrode. 0.64 Ni 0.36 / NiFe2O4-CDs, reference electrode Hg / HgO, counter electrode Pt; ORR uses 0.1mol / L KOH, OER uses 1mol / L KOH; ORR half-wave potential E 1 / 2 The voltage is 0.857V, and the OER is 10mA / cm. 2 The overpotential is 288mV.
[0057] The Fe obtained in Example 4 0.64 Ni 0.36 A liquid zinc-air battery was assembled using a NiFe2O4-CDs bifunctional oxygen electrocatalyst as the air cathode and a zinc sheet as the anode in a 6 mol / L KOH + 0.2 mol / L Zn(CH3COO)2 electrolyte. Charge-discharge cycle performance was tested at 20 mA / cm². 2 It can be stably cycled for 595 hours under constant current density; discharge polarization and power density tests were conducted, with a peak power density of 216 mW / cm². 2 A solid-state zinc-air battery assembled with sodium polyacrylate as the electrolyte was then subjected to charge-discharge cycle performance testing at a low temperature (-40℃), achieving a value of 2 mA / cm². 2 It can cycle stably for 392 hours at current density.
[0058] Example 5 A Fe 0.64 Ni 0.36 The preparation method of / NiFe2O4-CDs bifunctional oxygen electrocatalyst includes the following steps: (1) Weigh 10g of melamine and place it in a crucible. Cover the crucible and seal it with aluminum foil. Then, transfer the crucible into a muffle furnace. Under a closed reaction environment, heat the crucible to 570℃ at a heating rate of 2.8℃ / min and hold it for 5.2h. The thermal polymerization forms a graphite-like carbon nitride. After naturally cooling to room temperature, take out the product and grind it into fine powder. Then, put the fine powder into a crucible and seal it. Under a closed reaction environment, heat the crucible to 532℃ at a heating rate of 9.2℃ / min and hold it for 2.6h. After naturally cooling to room temperature, carbon nanosheets are obtained.
[0059] (2) A mixed solvent was prepared by mixing deionized water, ethanol, and methanol in a volume ratio of 3:1:2. Then, a solid iron source (3.2 mmol Fe(NO3)3·9H2O + 1.6 mmol FeSO4·7H2O + 0.14 mmol C6H8O7Fe + 0.1 mmol FePO4) and a nickel source (2.6 mmol Ni(NO3)2·6H2O + 1.6 mmol NiSO4·6H2O + 0.1 mmol C6H8O7Fe + 0.1 mmol FePO4) were added. 10 H 14 NiO4), carbon dot precursor (1.6 mmol citric acid + 2.6 mmol urea + 0.1 mmol o-phenylenediamine) and carbon nanosheets (100 mg) were dissolved in 57 mL of mixed solvent and ultrasonically dispersed for 0.82 h to form a homogeneous mixed solution. The resulting mixed solution was then transferred to a reaction vessel and placed in an oven at 173 °C for 7.3 h. After the reaction was completed, the mixture was cooled to room temperature.
[0060] (3) Transfer the cooled solution to a beaker, place it in a drying oven, and dry it at 88°C for 14 hours. Grind the resulting block sample for 28 minutes to obtain a fine powder sample.
[0061] (4) The powder sample was placed in a crucible and then transferred to a tube furnace. Under the protective atmosphere of a mixture of Ar and N2 (Ar to N2 volume ratio of 64:1), the temperature was increased to 882℃ at 2.8℃ / min and held for 2.8h to carry out a high-temperature pyrolysis reduction reaction. After the reaction was completed, the sample was cooled to room temperature to obtain Fe. 0.64 Ni 0.36 / NiFe2O4-CDs bifunctional oxygen electrocatalyst.
[0062] Fe prepared in Example 5 0.64 Ni 0.36 The / NiFe2O4-CDs bifunctional oxygen electrocatalyst was tested using a Bio-logic VMP-300 electrochemical station, with Fe as the working electrode. 0.64 Ni 0.36 / NiFe2O4-CDs, reference electrode Hg / HgO, counter electrode Pt; ORR uses 0.1mol / L KOH, OER uses 1mol / L KOH; ORR half-wave potential E 1 / 2 The voltage is 0.858V, and the OER is 10mA / cm. 2 The overpotential is 292mV.
[0063] The Fe obtained in Example 5 0.64 Ni 0.36 A liquid zinc-air battery was assembled using a NiFe2O4-CDs bifunctional oxygen electrocatalyst as the air cathode and a zinc sheet as the anode in a 6 mol / L KOH + 0.2 mol / L Zn(CH3COO)2 electrolyte. Charge-discharge cycle performance was tested at 20 mA / cm². 2 It can cycle stably for 593 hours under constant current density; discharge polarization and power density tests were conducted, and the peak power density was 217.6 mW / cm². 2 A solid-state zinc-air battery assembled with sodium polyacrylate as the electrolyte was then subjected to charge-discharge cycle performance testing at a low temperature (-40℃), achieving a value of 2 mA / cm². 2 It can cycle stably for 394 hours at current density.
[0064] Example 6 A Fe 0.64 Ni 0.36 The preparation method of / NiFe2O4-CDs bifunctional oxygen electrocatalyst includes the following steps: (1) Weigh 10g of melamine and place it in a crucible. Cover the crucible and seal it with aluminum foil. Then, transfer the crucible into a muffle furnace. Under a closed reaction environment, heat the crucible to 575℃ at a heating rate of 2.9℃ / min and hold it for 5.6h. Thermally polymerize to form graphite-like carbon nitride. After naturally cooling to room temperature, take out the product and grind it into fine powder. Then, put the fine powder into a crucible and seal it. Under a closed reaction environment, heat the crucible to 541℃ at a heating rate of 9.6℃ / min and hold it for 2.8h. After naturally cooling to room temperature, carbon nanosheets are obtained.
[0065] (2) A mixed solvent was prepared by mixing deionized water, ethanol, and methanol in a volume ratio of 3:2:1. Then, a solid iron source (3.6 mmol Fe(NO3)3·9H2O + 1.8 mmol FeSO4·7H2O + 0.16 mmol C6H8O7Fe + 0.1 mmol FePO4) and a nickel source (2.8 mmol Ni(NO3)2·6H2O + 1.8 mmol NiSO4·6H2O + 0.1 mmol C6H8O7Fe + 0.1 mmol FePO4) were added. 10 H 14NiO4), carbon dot precursor (1.8 mmol citric acid + 2.8 mmol urea + 0.1 mmol o-phenylenediamine) and carbon nanosheets (100 mg) were dissolved in 58 mL of mixed solvent and ultrasonically dispersed for 0.9 h to form a homogeneous mixed solution. The resulting mixed solution was then transferred to a reaction vessel and placed in an oven at 176 °C for 7.6 h. After the reaction was completed, the mixture was cooled to room temperature.
[0066] (3) Transfer the cooled solution to a beaker, place it in a drying oven, and dry it at 89°C for 14.5 h. After drying, grind the block sample for 29 min to obtain a fine powder sample.
[0067] (4) The powder sample was placed in a crucible and then transferred to a tube furnace. Under the protective atmosphere of a mixture of Ar and N2 (Ar to N2 volume ratio of 67:1), the temperature was increased to 890℃ at 2.9℃ / min and held for 2.9h to carry out a high-temperature pyrolysis reduction reaction. After the reaction was completed, the sample was cooled to room temperature to obtain Fe. 0.64 Ni 0.36 / NiFe2O4-CDs bifunctional oxygen electrocatalyst.
[0068] Fe prepared in Example 6 0.64 Ni 0.36 The / NiFe2O4-CDs bifunctional oxygen electrocatalyst was tested using a Bio-logic VMP-300 electrochemical station, with Fe as the working electrode. 0.64 Ni 0.36 / NiFe2O4-CDs, reference electrode Hg / HgO, counter electrode Pt; ORR uses 0.1mol / L KOH, OER uses 1mol / L KOH; ORR half-wave potential E 1 / 2 The voltage is 0.859V, and the OER is 10mA / cm. 2 The overpotential is 296mV.
[0069] The Fe obtained in Example 6 0.64 Ni 0.36 A liquid zinc-air battery was assembled using a NiFe2O4-CDs bifunctional oxygen electrocatalyst as the air cathode and a zinc sheet as the anode in a 6 mol / L KOH + 0.2 mol / L Zn(CH3COO)2 electrolyte. Charge-discharge cycle performance was tested at 20 mA / cm². 2 It can cycle stably for 591 hours under constant current density; discharge polarization and power density tests were conducted, with a peak power density of 219 mW / cm². 2 A solid-state zinc-air battery assembled with sodium polyacrylate as the electrolyte was then subjected to charge-discharge cycle performance testing at a low temperature (-40℃), achieving a value of 2 mA / cm². 2 It can cycle stably for 394.5 hours at the current density.
[0070] Example 7 A Fe 0.64 Ni 0.36 The preparation method of / NiFe2O4-CDs bifunctional oxygen electrocatalyst includes the following steps: (1) Weigh 10g of melamine and place it in a crucible. Cover the crucible and seal it with aluminum foil. Then, transfer the crucible into a muffle furnace. Under a closed reaction environment, heat the crucible to 580℃ at a heating rate of 3℃ / min and hold it for 6h. The thermal polymerization forms a graphite-like carbon nitride. After naturally cooling to room temperature, take out the product and grind it into fine powder. Then, put the fine powder into a crucible and seal it. Under a closed reaction environment, heat the crucible to 550℃ at a heating rate of 10℃ / min and hold it for 3h. After naturally cooling to room temperature, carbon nanosheets are obtained.
[0071] (2) A mixed solvent was prepared by mixing deionized water, ethanol, and methanol in a volume ratio of 1:3:2. Then, solid iron source (4 mmol Fe(NO3)3·9H2O + 2 mmol FeSO4·7H2O + 0.2 mmol C6H8O7Fe + 0.1 mmol FePO4) and nickel source (3 mmol Ni(NO3)2·6H2O + 2 mmol NiSO4·6H2O + 0.1 mmol C6H8O7Fe + 0.1 mmol FePO4) were added. 10 H 14 NiO4), carbon dot precursor (2 mmol citric acid + 3 mmol urea + 0.1 mmol o-phenylenediamine) and carbon nanosheets (100 mg) were dissolved in 60 mL of mixed solvent and ultrasonically dispersed for 1 h to form a homogeneous mixed solution. The resulting mixed solution was then transferred to a reaction vessel and placed in an oven at 180 °C for 8 h. After the reaction was completed, the mixture was cooled to room temperature.
[0072] (3) Transfer the cooled solution to a beaker, place it in a drying oven, and dry it at 90°C for 15 hours. After drying, grind the block sample for 30 minutes to obtain a fine powder sample.
[0073] (4) Place the powder sample in a crucible and then transfer it to a tube furnace. Under the protective atmosphere of a mixture of Ar and N2 (Ar to N2 volume ratio of 70:1), heat the sample to 900℃ at 3℃ / min and hold for 3h to carry out a high-temperature pyrolysis reduction reaction. After the reaction is completed, cool the sample to room temperature to obtain Fe. 0.64 Ni 0.36 / NiFe2O4-CDs bifunctional oxygen electrocatalyst.
[0074] Fe prepared in Example 7 0.64 Ni 0.36The / NiFe2O4-CDs bifunctional oxygen electrocatalyst was tested using a Bio-logic VMP-300 electrochemical station, with Fe as the working electrode. 0.64 Ni 0.36 / NiFe2O4-CDs, reference electrode Hg / HgO, counter electrode Pt; ORR uses 0.1mol / L KOH, OER uses 1mol / L KOH; ORR half-wave potential E 1 / 2 The voltage is 0.854V, and the OER is 10mA / cm. 2 The overpotential is 282mV.
[0075] The Fe obtained in Example 7 0.64 Ni 0.36 A liquid zinc-air battery was assembled using a NiFe2O4-CDs bifunctional oxygen electrocatalyst as the air cathode and a zinc sheet as the anode in a 6 mol / L KOH + 0.2 mol / L Zn(CH3COO)2 electrolyte. Charge-discharge cycle performance was tested at 20 mA / cm². 2 It can cycle stably for 599 hours under constant current density; discharge polarization and power density tests were conducted, with a peak power density of 218 mW / cm². 2 A solid-state zinc-air battery assembled with sodium polyacrylate as the electrolyte was then subjected to charge-discharge cycle performance testing at a low temperature (-40℃), achieving a value of 2 mA / cm². 2 It can cycle stably for 392.5 hours at the current density.
[0076] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A Fe 0.64 Ni 0.36 The method for preparing / NiFe2O4-CDs bifunctional oxygen electrocatalyst is characterized by, Includes the following steps: (1) Melamine was placed in a crucible and sealed. Then the crucible was moved into a muffle furnace and sintered for the first time under a closed reaction environment. The thermal polymerization formed graphite-like carbon nitride. After sintering, the furnace was naturally cooled to room temperature. The product was taken out and ground into fine powder. The fine powder was put back into the crucible and sealed. The second sintering was carried out under a closed reaction environment. The carbon nanosheets were obtained by naturally cooling to room temperature. (2) Prepare a mixed solvent using deionized water, ethanol and methanol, then dissolve the iron source, nickel source, carbon dot precursor and carbon nanosheets in the mixed solvent, and ultrasonically disperse them to form a uniform mixed solution. Then transfer the obtained mixed solution to the reaction vessel, put it in the oven for reaction, and cool it at room temperature after the reaction is completed. (3) The cooled solution is dried, and the resulting block sample is ground to obtain a fine powder sample; (4) Under an inert protective atmosphere, the powder sample was subjected to a high-temperature pyrolysis reduction reaction. After the reaction was completed, it was cooled to room temperature to obtain Fe. 0.64 Ni 0.36 / NiFe2O4-CDs bifunctional oxygen electrocatalyst.
2. The Fe as described in claim 1 0.64 Ni 0.36 The method for preparing / NiFe2O4-CDs bifunctional oxygen electrocatalyst is characterized by, In step (1), the heating rate of the first sintering is 2.5℃ / min~3℃ / min, the temperature is raised to 550℃~580℃ and held for 4h~6h; the heating rate of the second sintering is 8℃ / min~10℃ / min, the temperature is raised to 500℃~550℃ and held for 2h~3h.
3. The Fe as described in claim 1 0.64 Ni 0.36 The method for preparing / NiFe2O4-CDs bifunctional oxygen electrocatalyst is characterized by, In step (2), the ratio of iron source, nickel source, carbon dot precursor and carbon nanosheet is (3.2~6.3):(3.1~5.1):(3.1~5.1):
100. The iron source, nickel source, carbon dot precursor and carbon nanosheet form a solid mixture. The volume ratio of the sum of the molar amounts of iron source, nickel source and carbon dot precursor to the volume of the mixed solvent is (15.7~27.9):(50~60). The ultrasonic dispersion time is 0.5h to 1h, the reaction temperature in the oven is 160℃ to 180℃, and the reaction time is 6h to 8h.
4. The Fe as described in claim 1 0.64 Ni 0.36 The method for preparing / NiFe2O4-CDs bifunctional oxygen electrocatalyst is characterized by, In step (2), the iron source is a mixture of Fe(NO3)3·9H2O, FeSO4·7H2O, C6H8O7Fe and FePO4, and the nickel source is a mixture of Ni(NO3)2·6H2O, NiSO4·6H2O and C6H8O7Fe and FePO4. 10 H 14 A mixture of NiO4, with carbon dot precursors being a mixture of citric acid, o-phenylenediamine, and urea.
5. The Fe as described in claim 4 0.64 Ni 0.36 The method for preparing / NiFe2O4-CDs bifunctional oxygen electrocatalyst is characterized by, The molar ratio of Fe(NO3)3·9H2O, FeSO4·7H2O, C6H8O7Fe and FePO4 is (2~4):(1~2):(0.1~0.2):0.1; Ni(NO3)2·6H2O, NiSO4·6H2O and C 10 H 14 The molar ratio of NiO4 is (2-3):(1-2):0.1; The molar ratio of citric acid, urea, and o-phenylenediamine is (1-2):(2-3):0.1; The volume ratio of deionized water, ethanol and methanol is (1-3):(1-3):(1-3).
6. The Fe as described in claim 1 0.64 Ni 0.36 The method for preparing / NiFe2O4-CDs bifunctional oxygen electrocatalyst is characterized by, In step (3), the drying temperature is 80℃~90℃, the drying time is 12h~15h, and the grinding time is 20min~30min.
7. The Fe as described in claim 1 0.64 Ni 0.36 The method for preparing / NiFe2O4-CDs bifunctional oxygen electrocatalyst is characterized by, In step (4), the mixed protective gas is a mixture of Ar and N2, and the volume ratio of Ar to N2 is (50-70):
1. The high-temperature pyrolysis reduction reaction is carried out in a tube furnace. The tube furnace is heated to 850℃~900℃ at a heating rate of 2℃ / min~3℃ / min and held at that temperature for 2h~3h.
8. A Fe 0.64 Ni 0.36 / NiFe2O4-CDs bifunctional oxygen electrocatalyst, characterized in that... The Fe as described in any one of claims 1-7 0.64 Ni 0.36 The / NiFe2O4-CDs bifunctional oxygen electrocatalyst was prepared by a method for preparing the Fe 0.64 Ni 0.36 / NiFe2O4-CDs bifunctional oxygen electrocatalyst is a heterostructured porous carbon-based oxygen electrocatalytic material; Fe 0.64 Ni 0.36 Oxygen electrocatalytic performance of / NiFe2O4-CDs bifunctional oxygen electrocatalyst: Electrochemical ORR and OER were tested on a Bio-logic VMP-300 electrochemical station, with Fe 0.64 Ni 0.36 The NiFe2O4-CDs catalyst was used as the working electrode, the Hg / HgO electrode as the reference electrode, and the Pt electrode as the counter electrode. Electrochemical ORR and OER were measured using 0.1 mol / L KOH and 1 mol / L KOH solutions as electrolytes, respectively. For ORR, the half-wave potential (E...) 1 / 2 The voltage reaches 0.854V to 0.86V; for OER, 10mA / cm 2 At current density, the overpotential is 280mV to 300mV.
9. The Fe according to claim 8 0.64 Ni 0.36 Application of / NiFe2O4-CDs bifunctional oxygen electrocatalyst in zinc-air batteries.
10. The Fe as described in claim 9 0.64 Ni 0.36 The application of / NiFe2O4-CDs bifunctional oxygen electrocatalyst in zinc-air batteries is characterized by, With Fe 0.64 Ni 0.36 A liquid zinc-air battery was assembled using a NiFe2O4-CDs bifunctional oxygen electrocatalyst as the air cathode and a zinc sheet as the anode in a 6 mol / L KOH + 0.2 mol / L Zn(CH3COO)2 electrolyte. The battery operates at 20 mA / cm². 2 At current density, it achieves stable cycling for over 585 hours, with a power density ≥214.7 mW / cm². 2 A solid-state zinc-air battery was then assembled using sodium polyacrylate as the electrolyte, and tested at a low temperature of -40℃ and a current of 2 mA / cm². 2 Stable cycling for more than 390 hours at current density.